Evaluation of the Reactogenicity, Safety and Immunogenicity of the Domestic Influenza Inactivated Split FLU-M Vaccine in Immunization Adults aged 18–60 Years - I. V. Fel'dblyum; S. D. Novgorodova; G. M. Ignat'ev; S. O. Golodnova; V. P. Trukhin; S. Ya Melnikov (Эпидемиология и вакцинопрофилактика, 2018)
This article presents the results of a simple, blind, randomized, placebo-controlled, single-center, prospective research of the reactogenicity, safety, and immunogenicity of the domestic influenza inactivated split vaccine «Flu-M» in immunization of the adult population of 18–60 years old. Low reactogenicity, high safety profile and immunogenicity of the Flu-M vaccine were determined.